Diskursus Islam Kaffah - Lestari Nengsih; Aibdi Rahmat (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2022)
Islam brought by the Prophet Muhammad to the face of the earth since 14 centuries ago is to "introduce a paradigm of life that is oriented towards maintaining human dignity, saving, and making people happy. The paradigm of life that is meant is "comprehensive or comprehensive, involving beliefs about divinity, humanity, nature, and how to get a perfect life salvation. This paper seeks to examine the meaning of kaffah Islam by reviewing the meaning of the words Islam and kaffah, as well as to explore more deeply what are the teachings contained in kaffah Islam. In this study, the type of research used is library research with a qualitative descriptive approach. It can be concluded that Kaffah Islam is Islam that contains teachings that cover all aspects of life, about how the relationship between God and creatures is. In Islam, the source of teaching refers to the Qur'an and the Sunnah, the main teachings of Islam include aqidah/faith, sharia (worship and muamalah), then about morality.